Does Foreign Aid Reduce Poverty? : Empirical Evidence from Nongovernmental and Bilateral Aid - Yontcheva, Boriana; Masud, Nadia (Washington, D.C. : International Monetary Fund, 2005)
This paper assesses the effectiveness of foreign aid in reducing poverty through its impact on human development indicators. We use a dataset of both bilateral aid and NGO aid flows. Our results show that NGO aid reduces infant mortality and does so more effectively than official bilateral aid. The impact on illiteracy is less significant. We also test whether foreign aid reduces government efforts in achieving developmental goals and find mixed evidence of a substitution effect.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet